Effects of Technical Errors on the Outcomes of Operatively Managed Femoral Neck Fractures in Adults Less than 50 Years of Age. Issue 5 (May 2023) - Collinge, Cory A.; Finlay, Andrea; Harris, Payton; Rodriguez-Buitrago, Andres; de la Fuente, Guadalupe; Beltran, Michael; Mitchell, Phillip; Archdeacon, Michael; Tornetta, Paul; Mir, Hassan R.; Gardner, Michael; Sagi, H. Claude; et al.
Abstract : Objective: To evaluate the effect of technical errors (TEs) on the outcomes after repair of femoral neck fractures in young adults. Design: Multicenter retrospective clinical study. Setting: 26 North American Level 1 Trauma Centers. Patients: Skeletally mature patients younger than 50 years of age with 492 femoral neck fractures treated between 2005 and 2017. Intervention: Operative repair of femoral neck fracture. Main Outcome Measurements: The association between TE (malreduction and deviation from optimal technique) and treatment failure (fixation failure, nonunion, malunion, osteonecrosis, malunion, and revision surgery) were examined using logistic regression analysis. Results: Overall, a TE was observed in 50% (n = 245/492) of operatively managed femoral neck fractures in young patients. Two or more TEs were observed in 10% of displaced fractures. Treatment failure in displaced fractures occurred in 27% of cases without a TE, 56% of cases with 1 TE, and 86% of cases with 2 or more TEs. TEs were encountered less frequently in treatment of nondisplaced fractures compared with displaced fractures (39% vs. 53%, P < 0.001). Although TE(s) in nondisplaced fractures increased the risk of treatment failure and/or major reconstructive surgery (22% vs. 9%, P < 0.001), they were less frequently associated with treatment failure when compared with displaced fractures with a TE (22% vs. 69% P < 0.001). Conclusions: TEs were found in half of all femoral neck fractures in young adults undergoing operative repair. Both the occurrence and number of TEs were associated with an increased risk for failure of treatment. Preoperative planning for thoughtful and well-executed reduction and fixation techniques should lead to improved outcomes for young patients with femoral neck fractures. This study should also highlight the need for educational forums to address this subject. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.